Plants utilization by the communities of Bharsar and adjoining area of Pauri Garhwal District, Uttarakhand, India - ANAND S. BISHT; K. D SHARMA (Biodiversitas Journal of Biological Diversity, 2014)
Bisht AS, Sharma KD. 2014. Plants utilization by the communities of Bharsar and adjoining area of Pauri Garhwal District, Uttarakhand, India. Biodiversitas 15: 94-100. Garhwal Himalaya possesses luxuriant a varied vegetation with in the Himalaya region. Almost every plant has economic value in the form of shelter, food, water, medicine, fuel and industrial products and fodder. Surveys were conducted in entire Bharsar, Pauri Garhwal district of Uttarakhand, India in order to get information on traditional uses of plants by local inhabitants. A total of 138 plants were collected that some species had more than one function of which 39 species of vegetables, 28 species of medicinal plants, 19 species of fruits, 18 species of ornamental flowers, 12 species of forest plants, 7 species of agroforestry and social forestry, 8 species of spices and condiments, 6 species of minor cereal crop plants, 5 species of pulses, and 4 species of oil seed plants were found economically important as they are used by the people frequently for various purposes.